The Power of the Spoken Word in Defining Religion and Thought: A Case Study - Hilary Watt (Hmong Studies Journal, 2009)
This essay explores the relationship between religion and language through a literature review of animist scholarship and, in particular, a case study of the animist worldview of Hmong immigrants to the United States. An analysis of the existing literature reveals how the Hmong worldview (which has remained remarkably intact despite widely dispersed settlements) both informs and is informed by the Hmong language. Hmong is contrasted with English with regard to both languages’ respective affinities to the scientific worldview and Christianity. I conclude that Hmong and other "pre-scientific" languages have fundamental incompatibilities with the Western worldview (which both informs and is informed by dualistic linguistic conventions of modern language, a modern notion of scientific causality, and Judeo-Christian notions of the body/soul dichotomy). This incompatibility proves to be a major stumbling block for Western scholars of animist religion, who bring their own linguistic and cultural biases to their scholarship.